2007
DOI: 10.1063/1.2800840
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical crystallization of Fe-based amorphous alloys

Abstract: Mechanical alloying of a number of blended elemental powders of Fe-based alloy systems containing four or five components was undertaken to determine if amorphous phases could be produced and also to compare the glass-forming ability achieved by mechanical alloying and that obtained by solidification-processing methods. Amorphous phase formation was achieved in all the alloy systems investigated, the time for the amorphous phase formation being a function of the glass-forming ability of the alloy system invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…However, very long milling could imply recrystallization processes [22]. Results obtained in the present work show that even far beyond the time considered for stationary state using global techniques B inclusions are detected.…”
Section: Resultsmentioning
confidence: 56%
“…However, very long milling could imply recrystallization processes [22]. Results obtained in the present work show that even far beyond the time considered for stationary state using global techniques B inclusions are detected.…”
Section: Resultsmentioning
confidence: 56%
“…3) and total area of the main diffraction peak. As the figure indicates, the fraction of the amorphous phase abruptly increases up to 30 h of milling, then gradually increases up to 90 h of milling and finally decreases by increasing the milling time up to 120 h. The observed mechanically-induced amorphization for the current alloying system is attributed to different mechanisms, such as severe plastic deformation, grain refinement and particularly, the increase in the strain energy due to significant size difference between the constituent atoms [13,24]. Such parameters can increase the free energy of the crystals beyond that of hypothetical amorphous phase and consequently decreases the energy barrier for crystal-to-amorphous transformation [13,24,36].…”
Section: Powders Characterizationmentioning
confidence: 89%
“…The mechanically-induced crystallization and the formation of different phases including solid solutions and intermetallic compounds has been observed for other mechanically alloyed Fe-based amorphous powders [24,37]. It has been demonstrated that the temperature rise upon milling, powder contamination, introduction of mechanical energy and the corresponding variations in the thermodynamic stabilities of the different competing phases are the main causes of mechanical crystallization [13,24]. Moreover, it has been shown that the atomic displacement and enhancement of atomic mobility as a result of severe deformation upon milling contribute to deformation-induced crystallization [38].…”
Section: Powders Characterizationmentioning
confidence: 96%
See 2 more Smart Citations